IMPROVING GRADE VIII STUDENTS’ READING COMPREHENSION ACHIEVEMENT IN RECOUNT TEXT BY USING TWO STAY – TWO STRAY STRATEGY - Elvi Rodiana Dalimunthe; Meisuri (Universitas Negeri Medan, 2013)
This study deals with improving students’ reading comprehension through Two Stay – Two Stray Strategy. This study was conducted by using classroom action research. The subject of the research was class VIIIC MTs. Lab. IKIP Al- Wasliyah Medan which consisted of 34 students. The research was conducted in two cycles and every cycle consisted of four meetings and two meetings. The instruments for collecting data were quantitative data (multiple choice test) and qualitative data (diary notes, observation sheet, and interview). In test I, the mean score was 63.28. in test II, the mean score was 67.96. and in test III the mean score was 72.96. It can be concluded that Two Stay – Two Stray Strategy could improve students’ reading comprehension.